Produção mais limpa em um frigorífico de aves: aplicação da ferramenta SWOT - Uecker, Adriane Diemer (2013)
The constant search for improving the quality of life has gained importance worldwide. In this point of view, much emphasis is given to the production of healthier foods, in which chicken comes up as the most important animal protein in several countries. Regarding cleaner production, authors claim that it is an important tool for sustainable development, enabling savings in business and acting in accordance with environmental regulations. Based on this, this dissertation aimed to apply the SWOT analysis and the prioritization matrix for cleaner production practices in the production process of a poultry processing plant. In order to do this, we described the production process of the company, using the SWOT analysis and the prioritization matrix to diagnose strengths and weaknesses, opportunities and threats, in relation to cleaner production practices, and defining the correlation between internal and external factors, as well as motricity (influence) and impact. As the methodology, we used the exploratory research developed in a case study, having as the case unit a poultry processing plant in western Parana. As the result of this study, it was observed a situation of near neutrality in the development of cleaner production in the company, where the negative points are almost as many as the positive ones. It was concluded that the SWOT analysis and prioritization matrix are important tools for planning cleaner production, an essential stage for the development of business projects.